Lipid-based colloidal nanoparticles for applications in targeted vaccine delivery. Issue 7 (8th March 2023) - Khan, Muhammad Saad; Baskoy, Sila Appak; Yang, Celina; Hong, Joohye; Chae, Jayoung; Ha, Heejin; Lee, Sungjun; Tanaka, Masayoshi; Choi, Yonghyun; Choi, Jonghoon
Abstract : This review article demonstrated nucleic acid-based therapeutics and lipid nanoparticle type as a carrier of nucleic acid therapeutics for further applications of LNPs as flexible carriers in immuno-therapeutics and anti-cancer reagents. Abstract : Bioactive molecules and their effects have been influenced by their solubility and administration route. In many therapeutic reagents, the performance of therapeutics is dependent on physiological barriers in the human body and delivery efficacy. Therefore, an effective and stable therapeutic delivery promotes pharmaceutical advancement and suitable biological usage of drugs. In the biological and pharmacological industries, lipid nanoparticles (LNPs) have emerged as a potential carrier to deliver therapeutics. Since studies reported doxorubicin-loaded liposomes (Doxil®), LNPs have been applied to numerous clinical trials. Lipid-based nanoparticles, including liposomes, solid lipid nanoparticles (SLNs), and nanostructured lipid nanoparticles, have also been developed to deliver active ingredients in vaccines. In this review, we present the type of LNPs used to develop vaccines with attractive advantages. We then discuss messenger RNA (mRNA) delivery for the clinical application of mRNA therapeutic-loaded LNPs and recent research trend of LNP-based vaccine development.